Impact of pile‐driving and offshore windfarm operational noise on fish chorusing. Issue 1 (26th July 2021) - Siddagangaiah, Shashidhar; Chen, Chi‐Fang; Hu, Wei‐Chun; Pieretti, Nadia
Abstract: Offshore windfarms have recently emerged as a renewable energy solution. The effects of pile‐driving and long‐term impacts of operational noises on fish chorusing still, however, remain largely unknown. In this study, we investigated the variations of fish chorusing intensity and duration during the construction (2016) and operational phases (2017–2018) of a windfarm at the Eastern Taiwan Strait (ETS). At the ETS, two types of fish choruses (Types 1 and 2) were found to repeat over a diurnal pattern. In the 2 days after the pile driving, Type 1 chorusing showed lower intensity and longer duration, while Type 2 chorusing exhibited higher intensity and no changes in its duration. During the operational phases in 2017 and 2018, both choruses were longer in duration (2–3 h for Type 1; 0.5–1 h for Type 2). The intensity of Type 1 chorus increased by 5–10 dB, but no significant variation was recorded for Type 2. Our findings document, for the first time, different behavioral responses of two chorusing types exposed to pile‐driving and windfarm noise pressure. Fish choruses have been associated with several behavioral functions. Deviation from a regular pattern might affect fish reproductive success, cause migration, augmented predation, or physiological alterations. Because offshore windfarms installations are growing in magnitude and capacity worldwide, this study provides essential insights for policymakers and constitutes an important reference for assessing the effects of noise from pile driving and windfarms on fishes. Abstract : Offshore windfarms have recently emerged as a renewable energy solution. The effects of pile‐driving and the long‐term impacts of operational noises on fish chorusing, however, remain largely unknown. In this study, we investigated the variations of fish chorusing intensity and duration during the construction (2016) and operational phases (2017–2018) of a windfarm at the Eastern Taiwan Strait. Our findings document, for the first time, different behavioral responses of two fish chorusing types exposed to pile‐driving and windfarm noise pressure.